Jalan Tendem Menurunkan Resiko Jatuh Lansia - Arifiati, Retna Febri; Prasaja, Prasaja; Kurniawan, Hendri (Jurnal Terapi Wicara dan Bahasa, 2024)
Abstract Background: The aging process causes elderly people to experience functional changes. Some of these changes include neurological, sensory, musculoskeletal and cognitive changes. Some of these problems will have an impact on the elderly's ability to control their balance. One of the most influential factors in reducing the ability to control balance is the musculoskeletal system. Changes in the musculoskeletal system will reduce muscle mass and muscle strength. Decreased muscle mass results in slowness in movement, short footsteps, decreased muscle strength, especially in the lower extremities which experience balance problems and ultimately risk falling. Muscle weakness results in physical decline which is one of the main factors at risk of falls in the elderly. Tandem walking balance training is an exercise in posture or body position, controlling balance, muscle coordination and body movements as well as knowing the risk of falls that elderly people in Tohudan Wetan Village have. Objectives: This study aims to determine the effect of tandem walking balance training on the risk of falls in the elderly in Tohudan Wetan Village, Colomadu, Karanganyar. Methods: The design of this research is quantitative pre-experimental using a one-group pretest-posttest design. Sample selection used purposive sampling technique. Hypothesis testing using Paired Samples T Test. Result: The research results obtained a sig value. 0.000 (p<0.005) means that there is a significant influence on the risk of falls in the elderly before and after being given the tandem walking balance training intervention. Conclusion: This research shows that there is an effect of tandem walking balance training on the risk of falls in the elderly in Tohudan Wetan Village, Colomadu, Karanganyar. Key words: Tandem walking balance training, risk of falls, elderly